THE INFLUENCE OF AUGMENTED REALITY (AR) TECHNOLOGY, ADVERTISING APPEALS, LIVE SHOPPING, AND INFLUENCER MARKETING ON PURCHASING DECISIONS FOR HANASUI LIPSTICK PRODUCTS (CASE STUDY ON FEMALE STUDENTS IN LHOKSEUMAWE CITY) - Cut Dhea Fidela; Adnan; Naufal Bachri; Rahmaniar (CV. Radja Publika, 2025)
The present study investigates the influence of Augmented Reality (AR), advertising appeal, live shopping and influencer marketing on consumer purchasing decisions, with a specific focus on female university students in Lhokseumawe City as consumers of Hanasui lipstick products. The accelerated evolution of digital marketing platforms, in conjunction with the incorporation of interactive technologies, has profoundly influenced consumer behaviour, particularly within the cosmetics industry, where the experience of products holds particular significance. A purposive sampling method, categorised as non-probability sampling, was employed to select 120 respondents. The data were collected through an online questionnaire, which was distributed via Google Forms. The data were then analysed using multiple linear regression with SPSS version 21. The findings indicate that augmented reality (AR), advertising appeal, and live shopping features have a significant and positive influence on purchasing decisions, suggesting that immersive experiences and interactive product demonstrations enhance consumer confidence and interest. However, the investigation revealed that influencer marketing did not demonstrate a significant effect, suggesting that personal factors or peer recommendations may have a greater impact on consumer behaviour in this context than promotional content from influencers.